TREATMENT OF CHRONIC ADENOIDITIS IN CHILDREN - Ikramova F.S.; Jaxonov O.O. (International Journal of Artificial Intelligence for Digital Marketing, 2024)
The article describes various methods of removing adenoid hypertrophy, including aspiration diathermy, cold plasma surgery and a combined approach. The article analyzes in detail the combined approach, which is a more accurate, safe and effective method of removing adenoids, especially in children with palatine dysfunction. It describes how this method allows resecting lymphoid tissue with a cutter under clear visual endoscopic control, which avoids injury to the nasal septum, nasal conchs, posterior pharyngeal wall and tubal tonsils. The advantages of preserving the palatopharyngeal sphincter and controlling the depth of adenoid resection using this method are also discussed. In conclusion, it is noted that the combined approach based on the use of an endoscope is a promising method in the surgical treatment of adenoiditis in children with palatine dysfunction and can lead to improved results of surgery and reduced complications after it.